Association of voice and mental health diagnoses with differences in voice‐related care utilization. (11th September 2019) - Jordan, Victoria A.; Lunos, Scott; Sieger, Gretchen; Horvath, Keith J.; Cohen, Seth; Misono, Stephanie
Abstract : Objective: To compare healthcare utilization in voice patients with versus without mental health (MH) diagnoses Study Design: Retrospective study using electronic medical records from large regional healthcare system. Methods: We examined data on sociodemographic characteristics, comorbidities, voice‐related diagnoses, and patterns of healthcare utilization (including medication use, tests and procedures, and outpatient visits). The study period spanned January 2005 through June 2017. Results: A total of 24, 672 patients had at least one voice‐related diagnosis. Of these, 11, 483 (47%) also had at least one MH diagnosis compared to 14% in the overall repository ( P < 0.0001). The most common voice‐related diagnoses were nonspecific dysphonia (80%), acute laryngitis (30%), and vocal fold paresis/paralysis (7%). The 11, 483 patients with both voice‐related and MH diagnoses were more likely to have acute laryngitis and/or nonspecific dysphonia; less likely to have laryngeal cancer and/or paresis/paralysis; and more likely to have seen a primary care provider, to have received medications, and to have undergone radiology studies. In contrast, the 13, 189 patients with only voice‐related diagnoses had more overall voice‐related visits, were more likely to have seen an otolaryngologist, and were more likely to have undergone a voice evaluation with a speech language pathologist. Conclusion: Voice patients with MH diagnoses were less likely to see otolaryngology and more likely to have radiology studies than voice patients without MH diagnoses. Further study is warranted to characterize temporal sequences of care in this group of patients and determine whether these differences are attributable to referral patterns from primary care. Level of Evidence: 4 Laryngoscope, 130:1496–1502, 2020